Post-qualitative line of flight and the confabulative conversation: a methodological ethnography. Issue 4 (20th April 2016) - Johansson, Lotta
Abstract : This paper is a methodological ethnography aiming to highlight the difficulties in using conventional methods in connection with an explorative philosophy; Deleuze and Guattari's. Taking an empirical point of departure in conversations about the future with students in upper secondary school, the struggle to find a scientifically valid label through the focus group interview is outlined. However, combining the particular philosophy with a conventional qualitative method turned out to be an impossible aim since the ideals of the focus group interview departures in the image of stable subject simultaneously as the method is blemished by positivistic language and standards. By turning to post-qualitative research, which encourages new concepts and methods, the confabulative conversation was produced. Within these confabulative conversations, the aim has been to create a methodologically smooth space in order to enable movements beyond manifested knowledge in favor of the virtual and the not-yet-seen, and thus producing possibilities for something new.